2017
DOI: 10.5334/gjgl.348
|View full text |Cite
|
Sign up to set email alerts
|

How (not) to derive a *ABA: The case of Blansitt’s generalisation

Abstract: In this paper, I provide an account for the so-called Blansitt’s generalisation (Blansitt 1988). The generalisation says that in the linear sequence DATIVE—ALLATIVE—LOCATIVE, only adjacent functions may be marked the same. In previous work (Bobaljik 2012; Starke 2009; Caha 2009), analogous *ABA patterns have been encoded by the so-called feature cumulation. Feature cumulation means that the amount of features characteristic for individual categories monotonically grows in the order given in any such sequence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…For the exact notation used, the reader is referred to Bobaljik & Sauerland (2018). Caha (2017) builds on aspects of Bobaljik & Sauerland's (2018) explanation in order to explain a generalization from Blansitt (1988), who observes an ABA restriction in the case sequence dative-allative-locative. Rather than proposing a feature containment analysis [[[dative] allative] locative], Caha uses a so-called overlapping decomposition of features.…”
Section: Why *Aba?mentioning
confidence: 99%
See 2 more Smart Citations
“…For the exact notation used, the reader is referred to Bobaljik & Sauerland (2018). Caha (2017) builds on aspects of Bobaljik & Sauerland's (2018) explanation in order to explain a generalization from Blansitt (1988), who observes an ABA restriction in the case sequence dative-allative-locative. Rather than proposing a feature containment analysis [[[dative] allative] locative], Caha uses a so-called overlapping decomposition of features.…”
Section: Why *Aba?mentioning
confidence: 99%
“…In a sense, then, it may share present features with the present, and past features with the preterite. Such an intuition is particularly amenable to an analysis with overlapping decomposition (Caha 2017), which could be represented schematically as [present], [present, past], [past].…”
Section: (*)Aba In Germanic Verbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction. Recent work on morphology has investigated the absence of so-called ABA patterns of syncretism for various feature classes, including case, number, adjectival grade, and clusivity (Caha 2009(Caha , 2017Bobaljik 2012;McFadden 2018;Smith et al 2018;Moskal 2018, among others). In a hypothetical ABA pattern, a three-member 'paradigm' ordered by markedness sees the first and third share a form to the exclusion of the middle member.…”
mentioning
confidence: 99%
“…De Clercq (2013), De Clercq (2018b,a) found that syncretism patterns can be found between LSN and WSN markers that respect the *ABA generalisation (Johnston 1996, Caha 2009, Starke 2009, Bobaljik 2012, Caha 2017, Baunaz & Lander 2018. Bobaljik & Sauerland (2018:1-2) define *ABA as follows: The term *ABA generalization refers to morphological patterns in which, given some arrangement of the relevant forms in a structured sequence, the first and third may share some property 'A' only if the middle member shares that property as well.…”
Section: Negation and Syncretismsmentioning
confidence: 99%